Allah Yang Menderita sebagai Kekuatan Menghadapi Penderitaan - Bembid, Fransiskus Sailtus; Pidyarto Gunawan, Henricus; Saeng, Valentiuns (Studia Philosophica et Theologica, 2024)
This paper describes the suffering God as strength in facing suffering. This research departs from the philosophical-theological issues about evil and suffering in relation to the existence of God; If God exists why is there evil and suffering? Philosophy by using pure reason tries to keep looking for answers to the problem and the final answer is that there is no satisfactory answer. Whereas theology, based on revelation and with the help of reason, provides the final answer that closes the entire series of questions, namely that evil and suffering are mysteries. Humans will not get a definite answer to this problem, but one thing that is certain is that humans experience evil and suffering in the world. Therefore, there are two main problems involved in this research. First, what is the philosophical-theological view of the existence of God in relation to the phenomenon of evil and human suffering? Second, what is the Christian response to human suffering in light of the event of God suffering? This study uses a qualitative method with a doctrinal approach. This research more or less refers to the Encyclical Salvifici Doloris from John Paul II, the Encyclical Spe Salvi from Benedict XVI, and the book Iman Katolik: Buku Informasi dan Referensi from the Indonesian Bishops' Conference. This research found two things, first, Christ's suffering on the cross is proof of God's existence. Second, the God who suffers is strength in the face of suffering.